Bilateral Stress Fractures of the Femoral Neck after Total Knee Arthroplasty: Importance of Early Diagnosis - Sei Morinaga; Kenichi Ueshima; Yoshinobu Maruhashi; Noriyuki Hashimoto; Shoji Watanabe; Takuya Nakamura (Case Reports in Orthopedics)
Unilateral stress fracture of the femoral neck following total knee arthroplasty (TKA) is a rare complication; only 21 cases are described in English literature so far. Bilateral stress fractures of the femoral neck occurring simultaneously following a bilateral TKA have been seen in only 2 cases till now. We report a patient suffering from rheumatoid arthritis of both knees, who was treated with bilateral TKA. She developed spontaneous fractures of the femoral neck on both sides 12 months following the TKA. She was treated with bilateral total hip arthroplasty (THA). Stress fracture of the femoral neck should be suspected in patients complaining of hip pain who have undergone TKA.